2020
DOI: 10.1016/j.janxdis.2020.102314
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and OCD: Potential impact of exposure and response prevention therapy

Abstract: Highlights Some have suggested that ERP therapy for contamination OCD be paused during COVID-19. Discussion of how to modify but still provide robust ERP during COVID-19 is provided. ERP modified to follow public health guidelines is critical for treating OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 28 publications
0
33
0
4
Order By: Relevance
“…Several studies were conducted among adults with OCD during the COVID-19 period ( Banerjee, 2020 ; Benatti et al, 2020 ; Davide et al, 2020a ; French & Lyne, 2020 ; Kumar & Somani, 2020 ; Sharma et al, 2020 ; Sheu et al, 2020 ). Sharma et al ( Sharma et al, 2020 ) assessed adults with OCD two months after the COVID-19 outbreak in India, by using the Y- BOCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were conducted among adults with OCD during the COVID-19 period ( Banerjee, 2020 ; Benatti et al, 2020 ; Davide et al, 2020a ; French & Lyne, 2020 ; Kumar & Somani, 2020 ; Sharma et al, 2020 ; Sheu et al, 2020 ). Sharma et al ( Sharma et al, 2020 ) assessed adults with OCD two months after the COVID-19 outbreak in India, by using the Y- BOCS.…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports that examined OCS dynamics during the COVID-19 period, among adults with OCD that was stabilized prior to the COVID-19 outbreak, found exacerbation in cleaning compulsions ( French & Lyne, 2020 ; Kumar & Somani, 2020 ). A case report by Sheu et al ( Sheu et al, 2020 ) found that exposure and response prevention (ERP) therapy for a patient with contamination obsessions effective in reducing OCS and recommends continuation of ERP treatment during the current pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in this volume Cox, Jessup, Luber, and Olatunji (2020)) show that disgust proneness contributes to maladaptive anxiety responses and, in doing so, may represent a target for treatment. This work may also be informed by better understanding challenges that COVID-19 creates for the treatment of anxiety-related disorders, such as illustrated in this volume by Sheu, McKay, and Storch (2020)) regarding applications of exposure and response prevention for OCD during a pandemic.…”
Section: Evidence-based Intervention and Associated Challengesmentioning
confidence: 99%
“…A more recent challenge has emerged due to the COVID-19 pandemic. The stress from the pandemic and physical distancing is expected to increase both mental health symptoms and substance use, particularly among those already vulnerable to these conditions (Du et al 2020 ; McKay and Asmundson 2020 ). Emerging data (Czeisler et al 2020 ; McKay and Asmundson 2020 ) and anecdotal reports on implementation support calls support this concern.…”
Section: Case Study: Integrated Treatment Initiativementioning
confidence: 99%
“…The stress from the pandemic and physical distancing is expected to increase both mental health symptoms and substance use, particularly among those already vulnerable to these conditions (Du et al 2020 ; McKay and Asmundson 2020 ). Emerging data (Czeisler et al 2020 ; McKay and Asmundson 2020 ) and anecdotal reports on implementation support calls support this concern. Additionally, those with substance use disorders have higher rates of the comorbid health conditions that increase vulnerability to the impacts of COVID-19 (Farhoudian et al 2020 ; Volkow 2020 ).…”
Section: Case Study: Integrated Treatment Initiativementioning
confidence: 99%